Livelihood Security Vis-a-Vis Extension Needs of the Fishers Inhabiting around Rudrasagar Lake, Tripura - Biswarup Saha, (Indian Journal of Extension Education, 2023)
Tripura is blessed with an important wetland i.e. ‘Rudrasagar lake, declared as National Lake No. 13 andInternational Lake numbered 1572 as a Ramsar site. The lake is an important source of fish production andfish biodiversity of the state. However, the lake at present is under threat from a variety of human inducedchanges to their hydrology. In this study, 140 fishers were selected by simple random sampling method inthe vicinity of the lake, who are believed to be vulnerable as the resource base on which their livelihooddepends (i.e. the Rudrasagar lake) is in peril. Livelihood security index of active fishers was found 76.21 asagainst the seasonal fishers (62.18). Among the active fishers, majority of them (59.26%) were placed atmedium level of livelihood security index. Social security index of all the two classes were found to behighest among the livelihood security components. Environmental security as well as habitat security hada comparatively lower index value for both the classes. Most relevant extension needs of the fishers werealternative income generation and self-employment needs like initiation and development of differententerprises (Coefficient of relevance 0.88) followed by proper land use pattern in the vicinity of the lake(Coefficient of relevance 0.86) and conservation management of the lake (Coefficient of relevance 0.74).Skill development towards non-farm sector and sound availability of financial capital will motivate thefishers to diversify their livelihood to invest in other sector, expand their activities and smooth functioningof business. Making use of local knowledge in natural resource management, encouraging the use of moreselective and environmentally friendly fishing methods, stimulating income diversification towards nonfishingactivities, stimulating the development of microenterprises and offering microfinance support tothe fishers are some of the other suggestions of the study.